TO THE INVENTORY OF INVERTEBRATES OF THE VOLGA-URAL INTERFLUVES - Pavlova O. N., Fedotova A. A., Gulenko O. N., Krasheninnikov E. A., Gadalina D. S. (A breakthrough in science: development strategies, 2021)
Inventory of fauna has been carried out in the Volga-Ural interfluves and its part, the Samara region, for a long time. The necessity of fauna inventory has always been recognized by researchers, and now the problem has become of particular ecological urgency due to anthropogenic degradation of natural communities. Zoologists of the Samara region have achieved certain success in this direction.
Keywords: фауна; fauna; Волго-Уральское междуречье; Volga-Ural interfluves